Students' Satisfaction Level Towards Online Learning Compared To Traditional Classroom For English Subject - Ponto, Glen; Nurlaily, Nurlaily (Universitas PGRI Adi Buana Surabaya, 2020)
Amidst the COVID-19 pandemic, schools and universities in Indonesia are being closed down temporarily by the government. A shift from a traditional classroom has emerged. Online learning starts becoming the policy from the government until the COVID-19 issue ends. This study aims to examine the students’ satisfaction level in English subject at Universitas Internasional Batam towards online learning as opposed to traditional classrooms. Student satisfaction is an important parameter since it shows how they perform and engage in class. This research was conducted using a quantitative method. The sample of this study will be second-semester students who took English 2 subject. The data collection was done through google form questionnaires. The results of this study are expected to be a baseline for future improvement in online learning